Effect of Supply Chain Management on Organizational Performance of the Private Manufacturing Enterprises (PMEs) in South-East, Nigeria - Kifordu Anyibuofu Anthony (Faculty of Economics, Universitas Sriwijaya, 2018)
This study aimed at exploring the Effect of supply chain management on organizational performance of the Private manufacturing enterprises (PMEs) in South-East. To do so, the study used a questionnaire survey of the views of staff of selected companies on the subject matter. Secondary sources including textbooks, journals, unpublished work and other materials that related to the concept were also used. A sample size of 553 was derived from a total population of 1124 using Freund and William’s statistical formula. In this study, the content validity was used. The respondents interviewed as well as experts were approached face to face. Cronbach’s Alpha was used to test the reliability of the research instrument showing a result of 0.91. Two hypotheses were tested using Pearson product moment correlation and Regression analysis. The main findings of the study showed that training, technological know-how and security of investments enhance the development of innovative skills; also, opportunity identification positively promotes research and development significantly. The study concluded and recommended that firms need to ensure that their entrepreneurial abilities are developed consistently so that their survival will be ensured. Also that indigenous firm should engage in employment of qualified staff, though within their budget capacity.